Enhancing cancer‐associated fibroblast fatty acid catabolism within a metabolically challenging tumor microenvironment drives colon cancer peritoneal metastasis. Issue 5 (16th February 2021) - Peng, Shaoyong; Chen, Daici; Cai, Jian; Yuan, Zixu; Huang, Binjie; Li, Yichen; Wang, Huaiming; Luo, Qianxin; Kuang, Yingyi; Liang, Wenfeng; Liu, Zhihang; Wang, Qian; et al.
Abstract : Most cancer‐related deaths result from the progressive growth of metastases. Patients with peritoneal metastatic (PM) colorectal cancer have reduced overall survival. Currently, it is still unclear why colorectal cancer (CRC) cells home to and proliferate inside the peritoneal cavity, and there is no effective consolidation therapy for improved survival. Using a proteomic approach, we found that key enzymes of fatty acid oxidation (FAO) were decreased in patients with PM colorectal cancer. Furthermore, we confirmed that carnitine palmitoyltransferase IA (CPT1A), a rate‐limiting enzyme of FAO, was expressed at significantly low levels in patients with PM colorectal cancer, as determined by RT‐qPCR, IHC, and GEO dataset analysis. However, lipidomics revealed no difference in FFA levels between PM and non‐PM primary tumors. Here, we showed that cancer‐associated fibroblasts (CAFs) promote the proliferation, migration, and invasion of colon cancer cells via upregulating CPT1A to actively oxidize FAs and conduct minimal glycolysis. In addition, coculture‐induced glycolysis increased in cancer cells while fatty acid catabolism decreased with lower adiponectin levels. Importantly, inhibition of glycolysis significantly reduced the survival of CRC cells after incubation with conditioned medium from CAFs CPT1A ‐OE in vitro and impaired the survival and growth of organoids derived from CRC‐PM. Finally, we found that directly blocking FAO in CAFs CPT1A ‐OE with etomoxir inhibits migration and invasion in vitro and decreases tumor growth and intraperitoneal dissemination in vivo, revealing a role for CAF CPT1A in promoting tumor growth and invasion. In conclusion, our results suggest the possibility of testing FAO inhibition as a novel approach and clinical strategy against CAF‐induced colorectal cancer with peritoneal dissemination/metastases. Abstract : Patients with peritoneal metastatic (PM) colorectal cancer have reduced overall survival. In metabolically challenging tumor microenvironment, cancer‐associated fibroblasts (CAFs) enhance fatty acid catabolism by upregulating CPT1A expression and drive colon cancer peritoneal metastasis. Our results suggest the possibility of testing fatty acid oxidation inhibition as a novel approach and clinical strategy against CAF‐induced colorectal cancer with peritoneal dissemination/metastases.